2006
DOI: 10.1073/pnas.0609492103
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground sink strength in forests controls the allocation of carbon below ground and its [CO 2 ]-induced enhancement

Abstract: The partitioning among carbon (C) pools of the extra C captured under elevated atmospheric CO 2 concentration ([CO2]) determines the enhancement in C sequestration, yet no clear partitioning rules exist. Here, we used first principles and published data from four free-air CO2 enrichment (FACE) experiments on forest tree species to conceptualize the total allocation of C to below ground (TBCA) under current [CO2] and to predict the likely effect of elevated [CO2]. We show that at a FACE site where leaf area ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 49 publications
(14 reference statements)
7
107
2
Order By: Relevance
“…Despite many simplifications, such as keeping inherently dynamic parameters constant (e.g. the partitioning of C allocation between aboveground and belowground compartments, or stand mortality) (Palmroth et al 2006), process-based models deliver broad sets of output variables that forest managers may need to predict future forest development (Pretzsch 2009). Mäkelä & Valentine (2001) argue that stand-growth models can give correct answers for the wrong reasons, and that statistical calibration of such models should therefore be avoided whenever possible.…”
Section: Resultsmentioning
confidence: 99%
“…Despite many simplifications, such as keeping inherently dynamic parameters constant (e.g. the partitioning of C allocation between aboveground and belowground compartments, or stand mortality) (Palmroth et al 2006), process-based models deliver broad sets of output variables that forest managers may need to predict future forest development (Pretzsch 2009). Mäkelä & Valentine (2001) argue that stand-growth models can give correct answers for the wrong reasons, and that statistical calibration of such models should therefore be avoided whenever possible.…”
Section: Resultsmentioning
confidence: 99%
“…Allocation of carbon to fine roots is increased at high c i , suggesting an adaptive response to an overall increased N demand (e.g. Palmroth et al, 2006). Provided that N demands are met, increased c a should lead to increased NPP, and reduced c a should lead to reduced NPP, although changing allocation patterns might limit the magnitude of this response.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies at the Duke free-air CO 2 enrichment (FACE) site indicated that both elevated CO 2 and N fertilization altered soil microbial community composition based on phospholipid fatty acid (PLFA) profiling (Feng et al, 2010), whereas another study suggested that the bacterial community composition was more influenced by spatial variations than the CO 2 enrichment (Ge et al, 2010). Increased allocation of C (carbohydrates) into the soil under elevated CO 2 (Palmroth et al, 2006) and enhanced soil N availability with N fertilization have led to the shifts in the abundance and composition of soil microbial communities . Reports on the responses of AOB to elevated CO 2 are controversial in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, a four-year exposure to CO 2 in a FACE experiment site decreased the abundance of archaea but did not affect the population size of soil bacteria under trembling aspen (Lesaulnier et al, 2008). It was believed that elevated CO 2 increased plant photosynthetic rate and productivity, and the increase in the above-ground photosynthesis will result in greater below-ground C allocation via root exudation and rhizodeposition (Hungate et al, 1997;Jackson et al, 2009;Palmroth et al, 2006;Phillips et al, 2006), which can directly stimulate changes in the size and community structure of soil microorganisms (Drigo et al, 2009). However, no significant difference in DOC between ambient CO 2 and elevated CO 2 was observed in this study which was partly in consistent with the study of Jackson et al (2009), who found that no significant change of DOC between ambient and elevated CO 2 condition in the O horizon of soil.…”
Section: Responses Of Soil Bacterial and Archaeal Abundance To Elevatmentioning
confidence: 99%